Sustained levels of FGF2 maintain undifferentiated stem cell cultures with biweekly feeding. - Steven Lotz; Susan Goderie; Nicolas Tokas; Sarah E Hirsch; Faizzan Ahmad; Barbara Corneo; Sheila Le; Akhilesh Banerjee; Ravi S Kane; Jeffrey H Stern; Sally Temple; Christopher A Fasano (PLoS ONE, 2013)
An essential aspect of stem cell culture is the successful maintenance of the undifferentiated state. Many types of stem cells are FGF2 dependent, and pluripotent stem cells are maintained by replacing FGF2-containing media daily, while tissue-specific stem cells are typically fed every 3rd day. Frequent feeding, however, results in significant variation in growth factor levels due to FGF2 instability, which limits effective maintenance due to spontaneous differentiation. We report that stabilization of FGF2 levels using controlled release PLGA microspheres improves expression of stem cell markers, increases stem cell numbers and decreases spontaneous differentiation. The controlled release FGF2 additive reduces the frequency of media changes needed to maintain stem cell cultures, so that human embryonic stem cells and induced pluripotent stem cells can be maintained successfully with biweekly feedings.